Global warming collaborative study on strategies to limit CO2 [carbon dioxide] emissions in Asia and Brazil - Bhandari, Preety; Pachauri, R. K. (Tata McGraw-Hill Pub. Co., 1992)
Proceedings of a workshop held during Sept. 21-22, 1992 at New Delhi and organized by the Asian Energy Institute.